2022
DOI: 10.47750/pnr.2022.13.04.094
|View full text |Cite
|
Sign up to set email alerts
|

Intervention of Stunting Aged 0-59 Months Reviewing From Nutrition

Abstract: Nutritional intervention is an effort to overcome nutritional problems with programs such as giving Fe and calcium tablets to pregnant women, giving zinc to children. To find out the factors that cause stunting and the effectiveness of Nutrition Interventions in Stunting Toddlers. This type of research is survey research with a cross-sectional design. The research sample was children aged 0-59 months with short or very short criteria, totaling 60 respondents. Sampling technique is purposive. Data analysis thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
1
1
0
1
Order By: Relevance
“…This research is in line with research conducted by Nuraini & Iswati (2022) showing a p-value of 0.023 < of 0.05. So it can be said that there is a relationship between the history of exclusive breastfeeding and the incidence of stunting in toddlers 24-59 months in the work area of the Marawola Health Center (Ra'bung et al, 2022).…”
Section: The Relationship Between the History Of Exclusive Breastfeed...supporting
confidence: 92%
“…This research is in line with research conducted by Nuraini & Iswati (2022) showing a p-value of 0.023 < of 0.05. So it can be said that there is a relationship between the history of exclusive breastfeeding and the incidence of stunting in toddlers 24-59 months in the work area of the Marawola Health Center (Ra'bung et al, 2022).…”
Section: The Relationship Between the History Of Exclusive Breastfeed...supporting
confidence: 92%
“…Faktor ekonomi, sosial, politik, termasuk dalam basic factors; faktor keluarga, pelayanan kesehatan termasuk dalam underlying factors sedangkan faktor diet dan kesehatan termasuk dalam immediate factors. Pada penelitian sebelumnya dihasilkan ~ 100 ~ faktor resiko yang berkorelasi dengan kejadian stunting, yaitu riwayat pemberian ASI Eksklusif, riwayat pemberian MPASI, keanekaragaman kandungan nutrisi dan imunitas (Nuraini & Iswati, 2022). Faktor penyebab stunting adalah riwayat penyakit infeksi (ISPA dan Diare), Jenis pemberian MP-ASI, waktu pemberian MP-ASI.…”
Section: Pendahuluanunclassified
“…A study conducted by Nuraini et al (2022) revealed that factors such as a history of exclusive breastfeeding, complementary foods, diversity in food composition, nutritional adequacy, and immunity, had a significant effect on the risk of stunting among children 19,26 . This study clearly emphasized the importance of adequate nutritional intake to support optimal growth of children.…”
Section: Relationship Between Nutritional Status and The Incidence Of...mentioning
confidence: 99%